2020
DOI: 10.1016/j.ajp.2020.102213
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown of 1.3 billion people in India during Covid-19 pandemic: A survey of its impact on mental health

Abstract: Lockdown of 1.3 billion people in India during Covid-19 pandemic: A survey of its impact on mental health COVID-19 pandemic presented as a black swan event, and as a measure to curtail it the governments of different countries took various approaches (Tandon, 2020). However, most countries announced complete lockdown, with draconian travel and social restrictions. On March 24, 2020, the Government of India ordered a nationwide lockdown for 21 days, limiting movement of the entire population of 1.3 billion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 13 publications
(17 reference statements)
5
61
0
Order By: Relevance
“…Reported psychosocial distress due to COVID-19 was consistent with Gao et al ’s findings of anxiety and depression among Chinese communities ( Gao et al., 2020 ). Similarly, Kochhar et al found mental health concerns were related to isolation and income loss from lockdown ( Kochhar et al., 2020 ). The suggested benefit of Ramadan in reducing interactions and thus COVID-19 transmission due to people's low energy levels was mentioned elsewhere but lacks evidence ( Reza et al., 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…Reported psychosocial distress due to COVID-19 was consistent with Gao et al ’s findings of anxiety and depression among Chinese communities ( Gao et al., 2020 ). Similarly, Kochhar et al found mental health concerns were related to isolation and income loss from lockdown ( Kochhar et al., 2020 ). The suggested benefit of Ramadan in reducing interactions and thus COVID-19 transmission due to people's low energy levels was mentioned elsewhere but lacks evidence ( Reza et al., 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…A few qualitatively driven studies have used customised COVID-19 related questionnaires to survey the public on issues related to the psychological impact of COVID-19 on mental health. Some of these research studies have emerged from countries such as Australia [ 51 ], Spain [ 52 , 53 , 54 ], India [ 55 , 56 ], Mexico [ 57 ], China [ 58 , 59 , 60 , 61 ], United Kingdom [ 62 ], USA [ 63 ], and Italy [ 64 , 65 ]. Based on the completed virtual and web-based surveys, the outcomes from these surveys suggest that levels and rates of psychological distress vary across countries.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation, fear, uncertainty, economic turmoil is namely a few issues that can greatly cause psychological distress among humans due to COVID-19 [ 75 ]. In India poverty, starvation, hunger is still an issue that will be escalated due to COVID-19.…”
Section: Indian Scenario For Covid-19mentioning
confidence: 99%